2015
DOI: 10.4236/health.2015.712177
|View full text |Cite
|
Sign up to set email alerts
|

Global Standards and Local Policies for School Diabetes Care

Abstract: Objectives: The purpose of this study is to analyse the practical implementation of regional and national policies through the Protocol of Care of Children and Adolescents in School (2010) in Extremadura Region (Spain), and to compare its contents with the international standards of diabetes care at school defined by American Diabetes Association and International Diabetes Federation. The measures not only affect the security and diabetes care, but also inclusion and the right to health. Methods: A documental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The less than optimal results obtained from the study corresponds to results from other studies that have been conducted though all in developed countries to evaluate diabetes care in primary schools [21]. In general it has been shown that diabetes care is less than optimal in schools in the developed world [21] with the absence of specific policies [22]. Such studies have not been conducted in developing countries.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The less than optimal results obtained from the study corresponds to results from other studies that have been conducted though all in developed countries to evaluate diabetes care in primary schools [21]. In general it has been shown that diabetes care is less than optimal in schools in the developed world [21] with the absence of specific policies [22]. Such studies have not been conducted in developing countries.…”
Section: Resultssupporting
confidence: 54%
“…Such studies have not been conducted in developing countries. Even though Zimbabwe has a Schools Health Policy, specific policies are still required [22] that will ensure immediate safety, inclusion of the child in all activities, optimal academic performance and long term wellbeing. As this was a baseline, future studies can seek to standardize criteria for evaluating and defining optimal support services for the Zimbabwean context.…”
Section: Resultsmentioning
confidence: 99%
“…These policies should include details about adequate diabetes management (e.g., the frequency of and circumstances in which to perform blood glucose checks, appropriate times to administer insulin, planning for food intake and timing of snacks, recognition and management of symptoms of hypoglycemia and hyperglycemia, emergency plans and contacts, and information about participation in physical activities). The U.S. (35), Spanish (36), and Austrian (37) guidelines might serve as good examples.…”
Section: Implications and Conclusionmentioning
confidence: 99%